Copeptin to rule out myocardial infarction in Blacks versus Caucasians. Issue 5 (August 2019) - Beri, Neil; Daniels, Lori B; Jaffe, Allan; Mueller, Christian; Anand, Inder; Peacock, W Frank; Hollander, Judd E; DeFilippi, Christopher; Schreiber, Donald; McCord, James; Limkakeng, Alexander T; Wu, Alan H B; et al.
Background: Copeptin in combination with troponin has been shown to have incremental value for the early rule-out of myocardial infarction, but its performance in Black patients specifically has never been examined. In light of a potential for wider use, data on copeptin in different relevant cohorts are needed. This is the first study to determine whether copeptin is equally effective at ruling out myocardial infarction in Black and Caucasian races. Methods: This analysis of the CHOPIN trial included 792 Black and 1075 Caucasian patients who presented to the emergency department with chest pain and had troponin-I and copeptin levels drawn. Results: One hundred and forty-nine patients were diagnosed with myocardial infarction (54 Black and 95 Caucasian). The negative predictive value of copeptin at a cut-off of 14 pmol/l (as in the CHOPIN study) for myocardial infarction was higher in Blacks (98.0%, 95% confidence interval (CI) 96.2–99.1%) than Caucasians (94.1%, 95% CI 92.1–95.7%). The sensitivity at 14 pmol/l was higher in Blacks (83.3%, 95% CI 70.7–92.1%) than Caucasians (53.7%, 95% CI 43.2–64.0%). After controlling for age, hypertension, heart failure, chronic kidney disease and body mass index in a logistic regression model, the interaction term had a P value of 0.03. A cut-off of 6 pmol/l showed similar sensitivity in Caucasians as 14 pmol/l in Blacks. Conclusions: This is the first study to identify a difference in the performance of copeptin to rule out myocardial infarction between Blacks and Caucasians, with increased negative predictive value and sensitivity in the Black population at a cut-off of 14 pmol/l. This also holds true for non-ST-segment elevation myocardial infarction and, although numbers were small, similar trends exist in the normal troponin population. This may have significant implications for early rule-out strategies using copeptin.